Hexane insoluble fraction from purple rice extract retards carcinogenesis and castration-resistant cancer growth of prostate through suppression of androgen receptor mediated cell proliferation and metabolism - Ranchana Yeewa (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Prostate cancer and castration-resistant prostate cancer (CRPC) remain major health challenges in men. In this study, the inhibitory effects of a hexane insoluble fraction from a purple rice ethanolic extract (PRE-HIF) on prostate carcinogenesis and CRPC were investigated both in vivo and in vitro. In the Transgenic Rat for Adenocarcinoma of Prostate (TRAP) model, 1% PRE-HIF mixed diet-fed rats showed a significantly higher percentage of low-grade prostatic intraepithelial neoplasia and obvious reduction in the incidence of adenocarcinoma in the lateral lobes of the prostate. Additionally, 1% PRE-HIF supplied diet significantly suppressed the tumor growth in a rat CRPC xenograft model of PCai1 cells. In LNCaP and PCai1 cells, PRE-HIF treatment suppressed cell proliferation and induced G0/G1 cell-cycle arrest. Furthermore, androgen receptor (AR), cyclin D1, cdk4, and fatty acid synthase expression were down-regulated while attenuation of p38 mitogen-activated protein kinase, and AMP-activated protein kinase α activation occurred in PRE-HIF treated prostate cancer cells, rat prostate tissues, and CRPC tumors. Due to consistent results with PRE-HIF in PCai1 cells, cyanidin-3-glucoside was characterized as the active compound. Altogether, we surmise that PRE-HIF blocks the development of prostate cancer and CRPC through the inhibition of cell proliferation and metabolic pathways.